Pengaruh Kualitas Produk, Dan Distribusi, Terhadap Loyalitas Pelanggan PT. Mitra Karya Rawa Panjang Di Kota Bekasi - Yuliani, Adlina Shahibah Dewi; Hartono, Hartono (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aims to determine “The Effect of Product Quality and Distribution on Customer Loyalty at PT Mitra Karya Rawapanjang in Bekasi City. This research is quantitative research using descriptive methods. The sample in this study was 120 respondents. The sampling technique used in this study was saturated sampling technique. Each respondent was given 30 questions using a Likert scale. This research uses data analysis is Descriptive Test, Validity Test, Reabilitity Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Analysis, and Hypothesis Test, namely the t test and f test using SPSS Version 26. The results of this study indicate that with partial testing, Product Quality (X1) has a significant positive effect on Customer Loyalty (Y) of 30.5%, while distribution (X2) has a significant positive effect on Customer Loyalty (Y) of 22.3%, and simultaneously Product Quality (X1) and Distribution (X2) have a significant positive effect on Customer Loyalty (Y) of 38.0%, while the remaining 62% is influenced by other variables outside of this study.